Chromosomal variation and perinatal mortality in San Diego zoo Soemmerring's gazelles. Issue 4 (25th May 2015) - Steiner, Cynthia C.; Charter, Suellen J.; Goddard, Natalie; Davis, Heidi; Brandt, Margot; Houck, Marlys L.; Ryder, Oliver A.
<x xml:space="preserve">Abstract</x> Chromosomal translocations play a fundamental role in the evolution and speciation of antelopes (Antilopinae, Bovidae), with several species exhibiting polymorphism for centric fusions. For the past 35 years, the San Diego Zoo Global (SDZG) captive population of Soemmerring's gazelles has revealed complex karyotypes resulting from chromosomal translocations with diploid numbers ranging from 34 to 39. Poor reproductive performance of this species in captivity and elevated mortality the first month of life (perinatal) has been attributed to this chromosomal dynamism. We have extended the studies of karyotypic variation in the SDZG Soemmerring's gazelle population and analyzed the effect of chromosomal and genetic variation upon perinatal mortality. Karyotypes from 149 captive Soemmerring's gazelles were evaluated revealing two unreported autosomal combinations, now constituting a total of 15 distinct karyotypes for the 3 Robertsonian centric fusions originally described for this population. Among SDZG founders, distinct chromosomal variation and nuclear and mitochondrial genetic structure were detected corresponding to the institution of origin of the founders. Low levels of genetic distance and nucleotide diversity among individuals, in addition to high relatedness values, suggested that outbreeding is less of a concern than inbreeding for maintaining a sustainable captive population. Finally, analysis of karyotypes of offspring born into the SDZG Soemmerring's gazelle herds, in conjunction with the maternal karyotype showed association of chromosomal makeup with perinatal mortality. This supports the importance of continuing cytogenetic screening efforts, particularly to evaluate the presence of deleterious chromosomal rearrangements in stillborns. Zoo Biol. 34:374–384, 2015. © 2015 Wiley Periodicals Inc.